104k views
2 votes
What is the equation of the oblique asymptote.

h(x)=x^2-x-2/x+1


A.) y=x

B.) y=x-2

C.) y=x^2+1

D.) y=x+1

User Louissmr
by
4.9k points

2 Answers

1 vote

The asymptote of a curve is a straight line, to which curve in the case of distance to infinity approaches arbitrarily close.

If the curve given by the equation y = f (x) is reduced to infinity when x approaches a finite point a, then the line x = a is called the vertical asymptote of this curve.

x =
(x^(2) -x-2)/(x+1)

x =
(x^(2)-x-2 )/(x+1), x≠-1

x =
(x^(2) +x-2x -2)/(x+1)

x =
(x*(x+1) - 2 (x+1))/(x+1)

x =
((x+1) * (x-2))/(x+1)

x = x -2

0 = -2

x ∈ ∅

User Can Baycay
by
5.7k points
5 votes

Answer:

Option: B is the correct answer.

B.
y=x-2

Explanation:

The oblique asymptote occur when the degree of the numerator term is greater than the degree of the denominator term.

It is also known as the slant asymptote.

In order to find this we divide the numerator term by the denominator term and hence the resultant i.e. the quotient is the oblique asymptote.

Here we have a rational function as:


h(x)=(x^2-x-2)/(x+1)\\\\\\i.e.\\\\h(x)=(x^2-2x+x-2)/(x+1)\\\\i.e.\\\\h(x)=(x(x-2)+1(x-2))/(x+1)\\\\i.e.\\\\h(x)=((x+1)(x-2))/(x+1)\\\\i.e.\\\\h(x)=x-2

Hence, the oblique asymptote is:


y=x-2

What is the equation of the oblique asymptote. h(x)=x^2-x-2/x+1 A.) y=x B.) y=x-2 C-example-1
User JFreeman
by
5.8k points